Reliability of Goniometry‐Based Q‐Angle. Issue 9 (22nd March 2013) - Weiss, Lawrence; DeForest, Bradley; Hammond, Kelley; Schilling, Brian; Ferreira, Lucas
Abstract : Objective: To establish the stability reliability, precision, and minimum value for detecting real differences for quadriceps angle (Q‐angle) measurements based on standardized protocols and surface goniometry. Design: An intratester reliability study. Setting: University research laboratory. Participants: Fifty‐two healthy, young, relatively lean adults (25 men and 27 women) from the university community with no history of knee injury. Methods: Q‐angle was assessed with surface goniometry on 2 separate occasions separated by 48 hours. Subjects assumed a supine position with: (1) extended hips and knees, (2) neutral hip rotational position, (3) neutral foot position, and (4) isometrically contracted quadriceps femoris muscles. The axis of a manual extendable‐arm goniometer was placed over the center of the right patella with the proximal arm situated over the anterior‐superior iliac spine and the distal arm over the center of the tibial tuberosity. Main Outcome Measures: Stability reliability was calculated with use of intraclass correlation (ICC, 2‐way random model) and precision was calculated by standard error of measurement (SEM). The 95% limits of agreement also were calculated to estimate the minimum detectable difference in Q‐angles. The lowest acceptable ICC was set at ≥0.70 for stability reliability. Results: The following ICC (SEM) values were found: all subjects = 0.88 (1.0°), men = 0.77 (1.0°), and women = 0.85 (1.0°). The 95% limits of agreement were 3° for the same 3 groups. Conclusions: The surface goniometry protocol described herein appeared to be reliable for relatively lean young men and women. Although measures were precise to 1.0°, it appears a difference of 3° may be needed to detect a real difference in Q‐angles when measured in this fashion.